The behaviour of interlocking block beam: \b flexural strength - Sashitharan Subramaniam (School of Environmental Engineering, University Malaysia Perlis, 2012)
Interlocking block beams have been used as lintels to replace reinforced concrete beams in interlocking block construction. Normally mortar was used widely as the filler to hold the reinforcement and the block units to form homogeneous solid beam. Unfortunately the flexural strengths of these beams are low. This research presents the flexural strength of interlocking block beam assembled using G30 concrete by experimental testing and theoretical calculation. The result obtained was compared to control sample which was normal reinforced concrete of G30. Both type of beam were designed to have same dimension. The compressive strength for concrete and the comparison between grout and mortar also presented to determine the better filler. The results obtained from laboratory testing were validated with the calculation. The significance of using concrete filler for interlocking block beam compared to mortar and grout was determined by comparison of the flexural strength. The result shows that the flexural strength of interlocking block beam concrete as filler was 4401.21 kN/m2 where lesser than normal reinforced concrete beam which is 6161.175 kN/m2 but higher value compared grout and mortar.